An informal network of grafting experts to help the communities to conserve and utilize wild-aromatic pickle mango (Mangifera indica) diversity in the Central Western Ghats, India - Vasudeva, R.; Reddy, B.M.C.; Sthapit, B.R.; Ramanatha Rao, V. (International Society for Horticultural Science, 2015)
Wild-aromatic Pickle Mango (WPM) is a delicacy and an essential part of traditional culture of forest dwelling communities in the Western Ghats, India. This distinctive type of mango is sour and bitter with very unique and variable aromas. Harvested from the wild for household consumption and for sale in the central Western Ghats, India, it is a commodity of commerce. It is a major source of income for the rural farmers who are still dependent on the collection of WPM from the forest areas. Some individual households have obtained nearly INR45,000 (about US$ 700) by collection and sale of the WPM either collected from the forest or from their farms. For decades, farmers of the central Western Ghats have been experimenting with identifying and grafting WPM from the wild and ultimately verifying their performance on farm. However, several WPM types are still in the wild and their valuable diversity is shrinking because of harvesting. Network of grafting experts is a locally innovated system wherein a group of experts form an association and offer themselves to work in the farmersRSQUO field to graft rare and valuable WPM varieties. Through this network, farmers were able to collectively identify hundreds of varieties of pickle mangoes that exist in the forest. Overtime, this process has evolved from a social activity to an informal network of expert grafters who offer their expertise in grafting and maintaining pickle mangoes. In the process, hundreds of rare varieties have been conserved. It has the potential to enhance human and social capitals by capacity building, mobilizing awareness and contributing to the conservation of the species. We share the results of a unique initiative undertaken in the central Western Ghats to save these rare mango types.